Strategi Pengrajin dalam Melestarikan Tenun Pa'tannun asal Sa'dan Toraja Utara di Era Modern - Pongre'kun, Regina; Muhammad Zulfadli; Rusdi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The Craftsperson's Strategy in Preserving the Pa’tannun Weaving from Sa'dan North Toraja in the Modern Era. A thesis of the Social Science Education Study Program, Faculty of Social Sciences and Law, Universitas Negeri Makassar. Supervised by Muhammad Zulfadli and Rusdi This study aims to: (1) identify the strategies employed by artisans to preserve and sustain Tenun Pa’tannun as a form of local cultural heritage; and (2) analyze the strengths, weaknesses, opportunities, and threats that influence these preservation efforts. The preservation of Pa’tannun is essential not only because of its economic value but also due to its symbolic meaning, cultural significance, and its role as an expression of Torajan identity that is increasingly pressured by modernization. The results of the study indicate that (1) artisans implement key strategies to maintain the sustainability of Pa’tannun, including the transmission of traditional weaving skills to younger generations, design innovation and product diversification, as well as the use of digital promotion in the modern era. (2) Based on the SWOT analysis, the main strengths lie in the uniqueness of weaving techniques and the cultural meanings embedded in Pa’tannun, while the identified weaknesses include limited capital and the lack of regeneration among young artisans. Opportunities arise from the increasing public interest in ethnic products and cultural tourism, whereas threats stem from the development of the modern textile industry and the declining interest of younger generations in traditional crafts.